Kualitas Hidup Penderita Insomnia Pada Mahasiswa - Muhammad Akbar Nurdin; Andi Arsunan Arsin; Ridwan Mochtar Thaha (Faculty of Public Health, Hasanuddin University, Makassar, 2018)
Insomnia is a sleep disorder in the form of a recurring difficulty to sleep or maintaining sleep althoughthere are opportunities for it and the symptoms are typically followed by functional impairment while awake andactive in the daytime. One-third of adults experience difficulty in initiating sleep and maintaining sleep in a year,with 17% of them interfere with quality of life. This study aimed to determine the factors that affect the quality oflife of patients with insomnia at Hasanuddin University Post Graduate Students. This research type used crosssectional study. The research sample used the method of exhaustive sampling of 215 respondents who sufferfrom insomnia. Data were analyzed using path analysis. The results of the bivariate analysis showed that noeffect between smoking behavior of the level of insomnia with the coefficient of 0.425 and the quality of life withcoefficient -0.205. There was an effect of caffeine consumption on the level of insomnia with coefficient 0.392 andthe quality of life with coefficient -0.142.There was the influence of physical activity on the level of insomnia withcoefficient 0.192 and the quality of life with coefficient -0.409. The conclusion is the effect of smoking behavior,caffeine consumption and physical activity on insomnia level and quality of life.